Designing biochar properties through the blending of biomass feedstock with metals: Impact on oxyanions adsorption behavior. (January 2019) - Dieguez-Alonso, Alba; Anca-Couce, Andrés; Frišták, Vladimír; Moreno-Jiménez, Eduardo; Bacher, Markus; Bucheli, Thomas D.; Cimò, Giulia; Conte, Pellegrino; Hagemann, Nikolas; Haller, Andreas; Hilber, Isabel; Husson, Olivier; et al.
Abstract: Metal-blending of biomass prior to pyrolysis is investigated in this work as a tool to modify biochar physico-chemical properties and its behavior as adsorbent. Six different compounds were used for metal-blending: AlCl3, Cu(OH)2, FeSO4, KCl, MgCl2 and Mg(OH)2 . Pyrolysis experiments were performed at 400 and 700 °C and the characterization of biochar properties included: elemental composition, thermal stability, surface area and pore size distribution, Zeta potential, redox potential, chemical structure (with nuclear magnetic resonance) and adsorption behavior of arsenate, phosphate and nitrate. Metalblending strongly affected biochars' surface charge and redox potential. Moreover, it increased biochars' microporosity (per mass of organic carbon). For most biochars, mesoporosity was also increased. The adsorption behavior was enhanced for all metal-blended biochars, although with significant differences across species: Mg(OH)2 -blended biochar produced at 400 °C showed the highest phosphate adsorption capacity (Langmuir Qmax approx. 250 mg g −1 ), while AlCl3 -blended biochar produced also at 400 °C showed the highest arsenate adsorption (Langmuir Qmax approx. 14 mg g −1 ). Significant differences were present, even for the same biochar, with respect to the investigated oxyanions. This indicates that biochar properties need to be optimized for each application, but also that this optimization can be achieved with tools such as metal-blending. These results constitute a significant contribution towards the production of designer biochars. Highlights: Biomass metal-blending prior to pyrolysis as tool to develop designer biochars. Metal-blending leads to the formation of biochar-metal composites on the biochar surface. Biochar microporosity, corrected by the C content, is increased with metal-blending. Very different values of redox and Zeta potential are observed for the metal-enhanced biochars. Metal-enhanced biochars show higher oxyanion (PO4 3−, AsO4 3− ) adsorption capacity.